Digital and sustainable micro-housing for urban youth: developing a user-centered structural model of social, spatial, and technological preferences in Istanbul - Erturk, Omer Faruk; Markoc, Ilkim (SPRINGER, 2026)
This study investigates how spatial comfort and flexibility, social integration, and digital infrastructure shape sustainable micro-housing preferences among young adults aged 18-35 in the Be & scedil;ikta & scedil; district of Istanbul. It develops and empirically tests a user-centered micro-housing model informed by participatory design principles and broader debates on safe, affordable, and inclusive urban housing. Grounded in Self-Determination Theory, the Capability Approach, and the Unified Theory of Acceptance and Use of Technology, the study employed a two-phase design. In the first phase, survey data from 410 participants were analyzed using chi-square tests, one-way analysis of variance, exploratory factor analysis, and covariance-based structural equation modeling in order to identify the spatial, social, and technological drivers of digital micro-housing preferences. In the second phase, qualitative feedback from 51 participants was thematically coded and used to further assess and refine the proposed typology. The analysis combined chi-square tests, one-way analysis of variance, Tukey's honestly significant difference test, exploratory factor analysis, and covariance-based structural equation modeling, with mediation effects evaluated through bootstrap resampling. The final model demonstrated acceptable overall fit. The findings show that technological infrastructure and energy efficiency were the strongest predictors of willingness to live in digital micro-housing, followed by spatial comfort and flexibility, and safety and social cohesion. Together, these factors explained substantial variation in housing satisfaction and willingness to live, while housing satisfaction also played a significant mediating role. This study offers an empirically grounded, user-centered model for understanding digital micro-housing preferences among young adults in Be & scedil;ikta & scedil;, Istanbul. By integrating Self-Determination Theory, the Capability Approach, and the Unified Theory of Acceptance and Use of Technology within a single analytical framework, it contributes to a more multidimensional understanding of sustainable and participatory housing. The findings indicate that technological infrastructure, spatial flexibility, and socially secure shared environments play a central role in shaping housing satisfaction and willingness to live in digital micro-housing, highlighting their importance for youth-oriented housing design.
Keywords: Digital micro-housing; Young adults; Housing preferences; Structural equation modeling; Sustainable urban housing; SIZE; Environmental Sciences & Ecology; Public Administration; Urban Studies